The Impact of Nutrition and Fine Particulate Matter (PM2.5) on Inflammatory Responses in Individuals with Metabolic Syndrome: A Paired Case Study from Chiang Mai, Thailand - Wason Parklak; Hataichanok Chuljerm; Sawaeng Kawichai; Puriwat Fakfum; Putita Jiraya; Praporn Kijkuokool; Wiritphon Khiaolaongam; Pakaphorn Ngamsang; Sakaewan Ounjaijean; Kittipan Rerkasem; Kanokwan Kulprachakarn (Toxics)
Exposure to fine particulate matter (PM2.5) is linked to increased systemic inflammation, particularly in individuals with metabolic syndrome (MS). This study assessed the impact of nutrition and PM2.5 exposure on inflammatory markers in individuals with MS. A total of 50 participants (25 with MS, 25 healthy controls) were monitored during a high-PM2.5 exposure period (HEP) and a low-PM2.5 exposure period (LEP). Dietary intake, health assessments, and inflammatory markers—TNF-α, IL-6, and CRP—were evaluated. The MS group had significantly higher BMI, fasting blood glucose, and triglyceride levels and lower HDL-C than the healthy group (p < 0.01), but these parameters did not change significantly between the HEP and LEP. Notably, dietary fiber intake increased in the MS group during the LEP (p < 0.05). CRP levels were higher in the MS group and significantly decreased in both groups during the LEP (p < 0.05). IL-6 was higher in the MS group during the HEP but did not significantly change across periods. TNF-α showed no differences. Dietary fiber intake was inversely correlated with IL-6 and CRP in the healthy group and strongly correlated with CRP in the MS group (r = −0.403, p < 0.01). Antioxidant vitamins were inversely correlated with inflammation only in healthy participants. These findings suggest that an increased dietary fiber intake may help reduce PM2.5-induced inflammation, particularly in individuals with MS.